Histopathological and immunohistochemical studies on the influence of orally administration monosodium glutamate, a food additive dependent on time in vivo - Sherin Ramadan Hamad (Journal of Basic and Applied Zoology, 2022)
Abstract Background Monosodium glutamate is a widely used flavor enhancer/food additive in meat, fish, milk and cheese or vegetable origins. Our present study aimed to assess the effect of utilization monosodium glutamate on the cardiac, splenic, hepatic and renal organs in mice. Thirty animals were divided into three groups: control group; glutamate 10 treated groups and glutamate 15 treated group. The experimental period was two successive weeks. Results Oral administrations of monosodium glutamate for 10 days induced moderate histopathological changes in cardiac, splenic, hepatic and renal tissues and also resulted in significant increase of the nuclear factor-kB expression depend on time of administration as compared to the control group, while treatment with monosodium glutamate for 14 days resulted in severe histopathological changes as well as highly significant increase of the nuclear factor-kB expression as compared to the control group. Conclusions It could be concluded that oral administration of monosodium glutamate induced histopathological alterations, and cytotoxicity in cardiac, splenic, hepatic and renal tissues dependent on time.